Urban high school the future of city schools - Sablan, Marianne Sheena Sarah U.; De Leon, Ruby Teresa M. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
The new urban high school is a response to the need for new educational facilities incorporating the K to 12 Basic Education Curriculum implemented by the Department of Education. The urban context in which it is developed takes into account increasing rates of urbanization all over the country, which results to scarcity in buildable land and expensive land values in the urban area. Thus the design approach integrates the complex program required by the new education curriculum into a compact, middle rise high school. Moreover, the Urban High School is designed as a template for future urban schools. Located in a 2.04-hectare site in Commonwealth Avenue, Quezon City, the 12-storey high school has a gross floor area of 13,200 square meters. It could accommodate a total of 1020 students from the Junior and Senior High School levels, and houses a variety of learning spaces which include general teaching classrooms, science laboratories, industrial arts workshops, and various home economics laboratories. Its joint-use facilities integrate it into the urban community fabric by opening their use for non-school activities. Major design features of the school include: well designed-learning spaces, maximized utilization of day lighting and natural ventilation, and the integration of sustainable design system, ie, rainwater harvesting, solar energy utilization, and air quality control.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: school buildings -- Designs and plans